(3GdfWb Gdeaghe ef Cgd GdUeJ GdeYdhes - (3SQGL GdOjf CMeO Hf WZQ Hc GdOeTbj, GHf GdeXaQ Hcs
(3ChdgG (B:s
(3hHYO aEfi JPGcQJ eY HYV GdENhGf eeG hQO aj GdYde ef cdGe GdMLQ dehSi Hf YeQGf Ydjg GdSdGe hcdGe GdbJjd aj Hfj ESQGFjd Ydi YjOg s
(3BNQgG (B:s
(3Ke Cf BOe Med hdOg gGHjd Ydi Yfbg hgh HGc MRjf gh hMhi CQHYjf jheoG HcGAkoG TOjOkG eJhGdjkG hGddg SHMGfg hJYGdi CYde hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B655s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs